2021
DOI: 10.3390/app11062481
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Properties of Lactobacillus casei HY2782 Are Affected by the Fermentation Time

Abstract: Maintaining probiotic effectiveness represents the most important task for the development of functional foods. Gastrointestinal stability and intestinal adhesion properties comprise one criterion for probiotic selection. Here, we investigated the benefits of milk fermented with Lactobacillus casei HY2782 at different fermentation times. The probiotic strain used was L. casei HY2782 and the reference strain was L. casei ATCC393 for comparisons. The samples were fermented for 7 days at 30 °C. We determined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Probiotics taken by mouth reach the intestine through a stressful environment such as saliva, gastric juice, and bile salt. Thus, the high digestive viability and ability to attach to the intestine are consistent with the effectiveness of the probiotic strain [39,41]. The simulated GIT showed that HY7715 had a very high viability, especially in the intestinal environment, resulting in better digestive stability than the type strain (Figure 9A).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Probiotics taken by mouth reach the intestine through a stressful environment such as saliva, gastric juice, and bile salt. Thus, the high digestive viability and ability to attach to the intestine are consistent with the effectiveness of the probiotic strain [39,41]. The simulated GIT showed that HY7715 had a very high viability, especially in the intestinal environment, resulting in better digestive stability than the type strain (Figure 9A).…”
Section: Discussionsupporting
confidence: 58%
“…Although many LAB strains are used as probiotics, not all LAB are probiotics, and only strains that have secured gastrointestinal stability and biological safety can be proposed as probiotics [35,56]. The ability to attach to intestinal epithelium and survive in the digestive tract is one of the main criteria for the selection of probiotic strains [39]. Probiotics taken by mouth reach the intestine through a stressful environment such as saliva, gastric juice, and bile salt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…can act against pathogens through different mechanisms, namely by producing antibacterial substances like bacteriocins that prevent their replication, competition for scarce nutrients in the host, anti-adhesive and anti-invasive action, and competitive exclusion by obstructing the adherence of pathogens to host cell binding sites [ 87 , 88 ]. One of the great benefits that L. casei strains can possibly exert against the invasion ability of our tested strains of P. dorei and P. distasonis is its known capacity to promote the abundance of tight junction proteins and mucin [ 87 , 89 ]. The inability of L. casei DSM 20011 to inhibit the invasion of strain P. dorei PtFD16P1 requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It also has high efficiency of gut colonization, and promotes the host's epithelium and immune cells (Hill et al, 2018). Lactobacilus casei has been extensively studied as a fermentation starter culture, since it has various functions such as increasing the expression of interleukin 12 in dendritic cell, and preventing the toxic effect induced by particulate matter (Jung et al, 2021).…”
Section: Introductionmentioning
confidence: 99%